Guest editorial: computational fluid dynamics - Ranade, Vivek V.; Pareek, Vishnu (Asia-Pacific Journal of Chemical Engineering, 2008)

Generic framework for crystallization processes using the population balance model and its applicability - Shaikh, Latif J.; Bari, Atul H.; Ranade, Vivek V.; Pandit, Aniruddha B. (Industrial & Engineering Chemistry Research, 2015)
A generic modeling framework for batch cooling crystallization processes has been developed to understand the crystallization process from operational and modeling point of view. The generic framework for crystallization process modeling incorporates the characteristic dimensions of crystals and polymorphic transformation, as well as the hydrodynamic mixing effects in the crystallizer. This Polyhedral Polymorphic Multizonal Population Balance (PPMPBM) model considers bottom-up and top-down approaches for specific systems with specific targets. The PPMPBM framework allows switching between complex and simple models to study different crystallization systems with different scenarios and combination thereof. This framework uses gPROMS software (PSE, UK) and the Microsoft Excel front-end, along with the Polytope module in Matlab, to predict the crystal size and shape evolution as well as supersaturation profiles inside the crystallizer, which can be implemented for various crystallization systems.

Green approach to dye wastewater treatment using biocoagulants - Chethana, M.; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Raja, S.; Ranade, Vivek V. (ACS Sustainable Chemistry & Engineering, 2016)
The present study focuses on newer biocoagulants, bioformulations, and the understanding of coagulant behavior with biocoagulants in relation to chemical coagulants. Newer biocoagulants, seeds of Azadirachta indica (AI) and pads of Acanthocereus tetragonus, are discussed along with two known biocoagulants, Moringa oleifera and Cicer arietinum seeds. Dye removal studies were carried out using widely reported Congo red dye to facilitate easy comparison with other conventional coagulants and the effect of various parameters such as initial dye concentration, pH, coagulant dose, etc. are discussed in detail. The use of biocoagulant was found to be highly effective, and up to 99% dye removal was achieved for coagulant doses in the range of 300-1500 mg/L. It was also observed that coagulation is pH sensitive, similar to chemical coagulants. Although the biocoagulant dose is relatively higher than the conventional chemical coagulants, a good value for the sludge volume index, similar to 50 mL/g for 1 h and 30 min, respectively, was obtained for the two coagulants, Acanthocereus tetragonus and Moringa oleifera. A very high particle count compared to chemical coagulants was observed using a focused beam reflectance measurement. Bioformulation with chemical coagulants such as alum, ferric, and aluminum based coagulants can, not only lower doses of biocoagulants (up to one-third) but can also result in significant improvement in the coagulation performance, up to 50% or more.
Keywords: coagulation; dye removal; Effluent treatment; flocculation; pollution